2021
DOI: 10.1108/ejim-09-2020-0362
|View full text |Cite
|
Sign up to set email alerts
|

Alone but together: flow experience and its impact on creative output in LEGO® SERIOUS PLAY®

Abstract: PurposeDo LEGO® SERIOUS PLAY® (LSP) workshops result in improved experience of flow components as well as higher levels of creative output than traditional meetings (MEET)? This research studies the extent to which LSP, as a specialized material-mediated and process-oriented cocreative workshop setting, differs from MEET, a traditional workshop setting. Hypotheses for differences in individual flow components (autotelic behavior, happiness, balance), group flow components (equal participation, continuous commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…According to Primus & Jiang (2019), LSP facilitates developing novel and surprising solutions to problems. Zenk et al, 2021 conclude that LSP improves the creative team output.…”
Section: Lego Serious Playmentioning
confidence: 78%
See 1 more Smart Citation
“…According to Primus & Jiang (2019), LSP facilitates developing novel and surprising solutions to problems. Zenk et al, 2021 conclude that LSP improves the creative team output.…”
Section: Lego Serious Playmentioning
confidence: 78%
“…Because of these factors, it is easier to achieve a 'train of thought' or 'flow' within a team, i.e. building upon each other's ideas, known as interactional synchrony (Zenk et al, 2021). Furthermore, LSP stimulates commitment to the team, resulting in active participation in the decision-making.…”
Section: Lego Serious Playmentioning
confidence: 99%
“…Empirical evidence according to Primus and Sonnenburg [43] shows that in LEGO ® Serious Play ® the group flow of all participants is always associated with the flow of each individual participant. In their study on the creative outputs of LEGO ® Serious Play ® , Zenk et al [44] have shown that it is also the state of flow which dissolves existing hierarchies within groups.…”
Section: The Lego ® Serious Play ® Experiencementioning
confidence: 99%
“…Compared to other methods in qualitative research, like group discussions or focus groups, LEGO ® Serious Play ® is especially distinctive regarding the level of participation and the expected outcomes. As Zenk et al [44] have shown, LEGO ® Serious Play ® processes are highly inclusive as all participants are actively involved in sharing their knowledge, opinions, and ideas. Based on the assumption that "the answers are 'already in the room', [LEGO ® Serious Play ® ] invites participants to 'think with their hands' to build their understandings.…”
Section: Researching Vulnerable Groups With Lego ® Serious Play ®mentioning
confidence: 99%
See 1 more Smart Citation